BRINGING MEDICAL GENETICS TO THE PUBLIC: THE CHALLENGES FOR INDONESIAN MEDICAL FACULTIES - Catur Setiya Sulistiyana (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
-